Composite dietary antioxidant index and lung cancer risk: insights from the UK biobank - Yi Feng; Xiuxia Fu; Bo Cheng; Peiling Chen; Zixun Wang; Juan He; Xiangyuan Zheng; Xinyi Wu; Xin Bi; Minyu Dong; Jianxing He; Wenhua Liang (BMC Public Health)
Abstract Background Previous studies provided inconsistent results on the effects of antioxidant intake on lung cancer prevention. This study aimed to investigate the association between the composite dietary antioxidant index (CDAI), which calculated the dietary intake of manganese, selenium, zinc, vitamins A, C and E, and the risk of lung cancer. Methods Using prospective data from the UK Biobank, this study employed Cox proportional hazards regression models to evaluate the relationship between CDAI and lung cancer risk, and restricted cubic spline analyses were used to explore potential nonlinear associations. Multiplicative and additive interaction analyses were conducted to assess the joint effects of CDAI and smoking status on lung cancer risk. Results Among 201,316 participants over a median follow-up of 11.8 years, 1,229 new cases of lung cancer were identified. Multivariate analysis showed that participants in the highest quartile of CDAI had a significantly lower risk of lung cancer (HR: 0.70; 95% CI: 0.57–0.86; P < 0.001), compared with those in the lowest quartile. An interaction effect between CDAI and smoking status was noted (P = 0.001). Among former smokers, the hazard ratio was 4.58 (95% CI: 3.36–6.25; P = 8.42 × 10⁻22) in the lowest CDAI quartile and decreased to 2.60 (95% CI: 1.83–3.70; P = 1.10 × 10⁻⁷) in the highest quartile, compared to never smokers in the lowest CDAI quartile. Conclusion This study revealed a significant link between increased dietary antioxidant intake and a reduced risk of lung cancer, particularly in former smokers.